Morphology prediction and dissolution behavior of α-succinic acid in ethanol solution using molecular dynamic simulation: article - Abd Samad, Nurul Azzrin; Othman, Muhamad Fitri; Md. Azmi, Nik Salwani; Yusop, Siti Nurul’Ain (2018)
Succinic acid is a potential co-former to produce co-crystal, thus an understanding of the dissolution behavior of succinic acid crystal is crucial for designing the co-crystal. In this works, α-succinic acid was chosen as a model compound for this study regardless its attractive crystal chemistry and its diverse surface properties. The aims of this study are to analyze the morphology of succinic acid crystal (form A) and to simulate the dissolution behavior of succinic acid crystal (form A) in the ethanol solution using molecular dynamic simulation. Molecular dynamics simulations have been performed by using Material Studio 4.4 by ACCELERYS. The most suitable morphology of the crystal was found in the combination of ESP charges with CVFF potential function and the morphology shape is elongated hexagonal needle-like shape which gives good agreement with the experimental crystal shape. In this research work, the MD simulation of dissolution of α-succinic acid has been successfully carried out. The less morphological important facet and high attachment energy which located at the tip of the crystal tends to dissolve faster compare to the most morphological important crystalline facet.